PENGARUH OVERREACTION TERHADAP HARGA SAHAM - Umi Murtini; Yonathan K. Widyatmadja (Jurnal Riset Akuntansi dan Keuangan, 2011)
This research aims to test the impact of market over reaction toward share prices on winner portfolio and loser portfolio. This is done using market adjusted model. The result indicates that there is an impact on over reaction toward share prices for loser portfolio and winner portfolio shares. This indicates that capital market efficiency in Indonesia is not yet strong.Overreaction happening on winner portfolio differs from loser portfolio.Keywords: overreaction, winner portfolio, loser portfolio, market adjusted model